Catalytic and Photocatalytic Nitrate Reduction Over Pd-Cu Loaded Over Hybrid Materials of Multi-Walled Carbon Nanotubes and TiO2 - Silva, Cláudia G.; Pereira, Manuel F. R.; Órfão, José J. M.; Faria, Joaquim L.; Soares, Olívia S. G. P. (Frontiers in Chemistry, 2018)
TiO2 and carbon nanotube-TiO2 hybrid materials synthesized by sol-gel and loaded with 1%Pd–1%Cu (%wt.) were tested in the catalytic and photocatalytic reduction of nitrate in water in the presence of CO2 (buffer) and H2 (reducing agent). Characterization of the catalysts was performed by UV-Vis and fluorescence spectroscopy, temperature programed reduction, N2 adsorption and electron microscopy. The presence of light produced a positive effect in the kinetics of nitrate removal. Higher selectivity towards nitrogen formation was observed under dark condition, while the photo-activated reactions showed higher selectivity for the production of ammonium. The hybrid catalyst containing 20 %wt. of carbon nanotubes shows the best compromise between activity and selectivity. A mechanism for the photocatalytic abatement of nitrate in water in the presence of the hybrid materials was proposed, based in the action of carbon nanotubes as light harvesters, dispersing media for TiO2 particles and in charge carrier facilitators.